La contratación pública y la participación de artesanos en el GADM del cantón Chone, Período 2019 - Delgado Solórzano, Gema Valeria (2022)
Making public purchases transparent in Ecuador through inclusive and representative policies is the line that is currently being carried out in public sector institutions. In this context, this research aims to diagnose the participation of artisans in the contracting processes in the Municipal Government in Chone canton, an approach that was carried out using methods such as inductive and analytical, which allowed the facts to be constructed based on true information to obtain reliable and technical results, with the support of descriptive, bibliographic and field research, with interviews and surveys, which led to determine that the contracting processes in which the artisans participated, constituted a minimum proportion of the annual contracting plan of the Municipality in Chone, in addition, it was verified that the channels of communication for the contracting processes can be found on the pages www.chone.gob.ec and www.sercop.gob.ec, which is why there is a need to design an information plan that will equally benefit all the artisans in Chone canton, so that they comply with all the requirements and demands of public contracting and encourage participation in the processes of purchasing goods and services carried out by the Autonomous Municipal Government in Chone canton.